Power Quality Control for Mixed Renewable Energy Systems - Akkilah, Mohammed; Farsadi, Murtaza (Frontier Energy System and Power Engineering, 2021)
Electrical energy is one of the famous and easiest used forms of energy. Electrical energy can be converted to many forms of energy. With the development of technology, the dependency on the electrical energy has been increased greatly nowadays. Such as Computer and telecommunication networks field, railway network banking, post office, life support system are few application that just cannot run without electricity. In this article we will discuss the power quality issues for distributed generation systems based on renewable energy sources, as an example solar and wind energy. A brief explanation about the power quality issues is conducted here.This article starts with the power quality issues, followed by discussions of basic standards. A brief study of power quality in the power system, it includes the systems with dc and renewable sources are done in this article. In addition to the power quality monitoring techniques and its possible solutions for the power quality issues for the power system are briefly discussed. Later we will go through the analyzing step for the methods of mitigation of these problems using custom power devices, such as D-STATCOM, UPQC, UPS, TVSS, DVR, etc., for micro grid systems. As an example for the renewable energy systems, such as the statcom can be an efficient choice due to its several advantages, whereas the spinning reserve can enhance the power quality in traditional systems. Finally, we will discuss the power quality in dc systems. Two Main advantages for a DC system, is the Simple arrangements and higher reliability. Even though it faces many power quality issues such as, instability and poor detection of faults.